Sixties Rock: Garage, Psychedelic, and other Satisfactions - Hicks, Michael (Urbana, IL University of Illinois Press, 2000)
Unlike their rock 'n' roll predecessors, many rock musicians of the mid-sixties came to consider themselves as artists, as self-conscious makers of a new sonic medium. Sixties Rock offers a provocative look at these artists and their innovations in two pivotal rock genres: garage rock and psychedelic music. Delving into everything from harmony to hardware, Michael Hicks shows what makes this music tick and what made it unique in its time. Now available for the first time in paperback, this "angular portrait" of an essentially experimental music illuminates the art of rock in the 1960s."A thoughtful, compelling, and stimulating addition to the literature of popular music studies. Hicks engages the musical details of rock music exceptionally well, accounting for their production and interpreting their significance. We need more such work."--Robert Walser, author of Running with the Devil: Power, Gender, and Madness in Heavy Metal Music "A fresh and fascinating account of an important body of American music. . . . Hicks's book rings true, much more than anything else I've read on the subject."--Charles Hamm, author of Putting Popular Music in Its Place "A delightful book, covering selected facets of a large musical era in considerable and highly readable detail."--Frank Oglesbee, Communication Booknotes QuarterlyMichael Hicks, a professor of music at Brigham Young University, is the author of Mormonism and Music: A History
Keywords: 20th Century (1901-2000); Popular music; Music history